Engineering a Methyllysine Reader with Photoactive Amino Acid in Mammalian Cells() - Arora, Simran (Chem Commun (Camb), 2020)
Methyllysine sites in proteins are recognized by an array of reader domains that mediate protein-protein interactions for controlling cellular processes. Herein, we engineer a chromodomain, an essential methyllysine reader, to carry 4-azido-L-phenylalanine (AzF) via amber suppressor mutagenesis and demonstrate its potential to bind and crosslink methylated proteins in human cells. We further develop a first-of-its kind chromodomain variant bearing two AzF units with enhanced crosslinking potential suitable for profiling the transient methyllysine interactome.